Pressure generated by syringes: Implications for hydrodissection and injection of dense connective tissue lesions - Hayward, W.; Haseler, Luke; Kettwich, L.; Michael, A.; Sibbitt, W.; Bankhurst, A. (Taylor & Francis, 2011)
Objective: Hydrodissection and high-pressure injection are important for the treatment of dense connective tissue lesions including rheumatoid nodules, Dupuytren's contracture, and trigger finger. The present study determined the optimal syringes for high-pressure injection of dense connective tissue lesions. Methods: Different sizes (1, 3, 5, 10, 20, and 60 mL) of a mechanical syringe (reciprocating procedure device) with a luer-lock fitting were studied. Twenty operators generated maximum pressure with each mechanical syringe size, and pressure was measured in pounds per square inch (psi). Subsequently, 223 dense connective tissue lesions were injected with different sizes of syringes (1, 3, or 10 mL). Outcomes included (i) successful intralesional injection and (ii) clinical response at 2 weeks.Results: Smaller syringes generated significantly more injection pressure than did larger syringes: 1 mL (363 ± 197 psi), 3 mL (177 ± 96 psi), 5 mL (73 ± 40 psi), 10 mL (53 ± 29 psi), 20 mL (32 ± 18 psi), and 60 mL (19 ± 12 psi). Similarly, smaller syringes were superior to larger syringes for intralesional injection success: 10 mL: 34% (15/44) vs. 1 mL: 100% (70/70) (p < 0.001) and 3 mL: 91% (99/109) (p < 0.001).Conclusion: Smaller syringes (≤ 3 mL) are superior to larger syringes (≥ 5 mL) for successful hydrodissection and high-pressure intralesional injection of dense connective tissue lesions. © 2011 Informa Healthcare on behalf of The Scandinavian Rheumatology Research Foundation.